Aggressive Behavior in Combat Veterans with Posttraumatic Stress Disorder - Begić, Dražen (Array, 2001)
The incidence of aggression and violent behavior in combat veterans varies can be observed with regard to the presence or absence of post-traumatic stress disorder (PTSD). Significantly greater occurence of aggression was observed in combat veterans with PTSD compared with those without PTSD. There are various types of aggressive behavior that frequently are combined. Autoaggressive (suicidal) and heteroaggressive (interpersonal violence) behaviors predominate, with dominating verbal aggression and impulsive somatic reactions. Impulsive reactions are more frequently directed toward unknown persons, whereas verbal aggression is mostly aimed at known people. In the occurence of aggressive behavior in combat veterans with PTSD, important roles are played by education level, low socioeconomic status, maltreatment in childhood, and previous types of violent behavior (before partcipation in war events).